Modern Language Situation in the Irkutsk Region: the Reasons for the Language Shift (based on the Material of Russian and Buryat Languages) - I. V. Evseeva; A. M. Kulekhova (Научный диалог)
The study of the language situation in the Irkutsk region (Ust-Orda Buryat district, Olkhonsky district, Odinsk village of the Angarsk region) is presented, where Russian and Buryat languages are closely interacting (Buryats are the second largest population after Russians in the designated territory). The linguistic situation of these districts of the Irkutsk region was first subjected to a comprehensive description (earlier in the Buryat linguistics the interaction of the Russian and Buryat languages was studied in other territories - the Republic of Buryatia, Aginsky Buryat District of the Chita Region). In the course of expeditionary research, we obtained information about in which functional areas the Buryats use their native language with the unconditional leadership of the Russian language. It was revealed that at present subordinate bilingualism is observed in this territory, leading to a gradual linguistic shift, which is observed at all levels of the Buryat language system. Among the indicators that contribute to the language shift, same as N. B. Vakhtin and E. V. Golovko, the authors distinguish the following: the number of speakers of the Buryat language, the language environment, type of economic activity, reproduction of the language, interethnic marriages, the state language policy, the prestige of the language, the presence or absence of writing. It is noted that each of these parameters shows a tendency towards the loss of the autochthonous language of the indigenous population.